Roll of thunder, hear my cry - Taylor, Mildred D. (New York : Dial Books, 2001)
A black family living in Mississippi during the Depression of the 1930s is faced with prejudice and discrimination which its children do not understand.
Sequel: Let the circle be unbroken.
Foreward by Mildred D. Taylor, 2001.
920
Accelerated Reader AR
Newbery Medal, 1977.
Keywords: Newbery Medal; African Americans -- Juvenile fiction; Logan family (Fictitious characters : Taylor) -- Fiction; Prejudices -- Juvenile fiction; Depressions -- 1929 -- Juvenile fiction; African Americans -- Fiction; Prejudices -- Fiction; Depressions -- 1929 -- Fiction; Mississippi -- Juvenile fiction; Mississippi -- Race relations -- Fiction; Mississippi -- Fiction